(untitled) (De Musica, 2024)
In 1961, the ethnomusicologist Diego Carpitella developed the concept of indifference to define the particular attitude that the poet-storytellers of Southern Italy have towards the musical dimension. With indifference, Carpitella certainly did not mean to argue that the musical aspect was not important in the economy of knowledge, art and the spectacle of the storytellers, but rather that music played functions that were not only reducible to aesthetics. Starting from a brief historical-anthropological description of the phenomenon of the Southern storytellers and the transformations it had from the early twentieth century, this contribution highlights the critical and exploratory role that music plays in the multimedia poetics of the storytellers of Southern Italy, aimed at finding, reflecting and denouncing the most controversial aspects of each story in the public dimension, as alienating as it is participatory, of the square.